Impact of Salinity Stress (NaCL) And AM Fungi on Growth and Yield of Onion (Allium Cepa L.) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
In the twenty-first century, agriculture industry faces several critical challenges, including the need to enhance crop immunity, reduce the dependance on chemical fertilizers, synthetic pesticides and herbicides and most importantly, improve overall crop yield and quality. Onion is one of the significant crops which is widely cultivated in Maharashtra. Maharashtra produces around 8.6 million tons of onions annually. Onion is commonly used as an edible vegetable and essential role in everyday cooking. Nowadays it is important to increase quality and quantity of onion is the need of society. The am fungi significantly enhanced the yield and quality and quantity of crop. The aim of present study to understand the impact of salinity and AM fungi on production of Onion for this purpose we use arbuscular mycorrhizal (AM) fungal species such as Acaulospora spinosa, Glomus fasciculatum, Glomus mosseae, and Gigaspora candida to increase the productivity of onion to examined how salt affects the growth of onion. The treated plots are compared with untreated plots. The treatments included onion crop with AM fungi with salt (NaCl) and crop without AM fungi with salt, to see how each group responded to salt stress.The experiment evaluated the effects of mycorrhizal fungi under NaCl-induced salinity on onion plants compared to non-mycorrhizal (non-AM) plants exposed to the same conditions. The findings revealed that non-AM plants exhibited significantly lower yields than those inoculated with AM fungi.The findings of study show positive effects of treatment on Onion crop showed consistently better growth than non-inoculated plants under all levels of salt stress. Increasing NaCl concentrations reduced leaves, roots, shoot/root length, and biomass, but AM-treated plants maintained significantly higher values. AM fungi notably improved bulb fresh and dry weight compared to plants without AM under the same salt levels. Overall, AM inoculation effectively mitigated the negative impact of salinity on onion plant growth.The present study was conducted during the period from October 2023 to January 2024. During the winter season, characterized by moderate daytime temperatures, distinctly cooler nights and low humidity.